Emprendimiento como promotor del crecimiento regional (2020)
The research aims to identify how entrepreneurship contributes to the growth of the region and know the entrepreneurial factors that promote regional development to encourage and strengthen the creation of new companies, for this a qualitative methodology is applied, beginning with the study of concepts such as entrepreneurship, economic development, and its relationship; several authors give importance to the entrepreneurship to contribute to the development of the country. Documents of the Cámara de Comercio del Cauca are reviewed, with the purpose of knowing the growth of companies created in Cauca during 2015-2017; finding the generation of small and medium-sized enterprises, especially in the commercial sector located in the center and adjacent sectors of Popayán, while the industrial sector is located to the north of the department of Cauca, then it is applied to the entrepreneurs a semi-structured interview to know the importance of innovation and its contribution to regional development. The result is that the entrepreneurship is considered a promoter of the economy; fosters enterprise creation, increases jobs and improves the economic and social development; it is necessary to train entrepreneurs to achieve innovative and competitive enterprises, identify and coordinate resources contributing welfare and wealth to society. Concluding that entrepreneurs must turn profitable business ideas with new products or services, look for new markets, and innovate; it is important to train and promote entrepreneurs to contribute to economic growth.